None Questions

Question Number 134546 by mohammad17 last updated on 05/Mar/21

$$\int_{\mathrm{0}} ^{\:\infty} \frac{{dx}}{\mathrm{1}+{e}^{{x}^{\mathrm{2}} } }\:\:{by}\:{two}\:{method} \\$$

Answered by Dwaipayan Shikari last updated on 05/Mar/21

$$\int_{\mathrm{0}} ^{\infty} \frac{{dx}}{\mathrm{1}+{e}^{{x}^{\mathrm{2}} } }\:\:\:\:\:\:\:\:{x}^{\mathrm{2}} ={u} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\infty} \frac{{u}^{−\frac{\mathrm{1}}{\mathrm{2}}} }{\mathrm{1}+{e}^{{u}} }{du}=\frac{\mathrm{1}}{\mathrm{2}}\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\left(−\mathrm{1}\right)^{{n}+\mathrm{1}} \int_{\mathrm{0}} ^{\infty} {e}^{−{nu}} {u}^{−\frac{\mathrm{1}}{\mathrm{2}}} {du} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\left(−\mathrm{1}\right)^{{n}+\mathrm{1}} \frac{\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}\right)}{{n}^{\frac{\mathrm{1}}{\mathrm{2}}} }=\frac{\mathrm{1}}{\mathrm{2}}\zeta\left(\frac{\mathrm{1}}{\mathrm{2}}\right)\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{2}^{\frac{\mathrm{1}}{\mathrm{2}}−\mathrm{1}} }\right)\sqrt{\pi}=\frac{\sqrt{\pi}}{\mathrm{2}}\zeta\left(\frac{\mathrm{1}}{\mathrm{2}}\right)\left(\mathrm{1}−\sqrt{\mathrm{2}}\right) \\$$

Commented by mohammad17 last updated on 05/Mar/21

$${sir}\:{whats}\:{the}\:{value}\:{or}\:{formulla}\:{of}\:\:\zeta \\$$

Commented by Dwaipayan Shikari last updated on 05/Mar/21

$$\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\left(−\mathrm{1}\right)^{{n}+\mathrm{1}} \frac{\mathrm{1}}{{n}^{{s}} }=\zeta\left({s}\right)\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{2}^{{s}−\mathrm{1}} }\right) \\$$

Answered by mathmax by abdo last updated on 05/Mar/21

$$\Phi\:=\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{dx}}{\mathrm{1}+\mathrm{e}^{\mathrm{x}^{\mathrm{2}} } }\:\:\mathrm{we}\:\mathrm{do}\:\mathrm{the}\:\mathrm{changement}\:\mathrm{x}^{\mathrm{2}} =\mathrm{t}\:\Rightarrow \\$$$$\Phi\:=\int_{\mathrm{0}} ^{\infty} \:\:\:\frac{\mathrm{dt}}{\mathrm{2}\sqrt{\mathrm{t}}\left(\mathrm{1}+\mathrm{e}^{\mathrm{t}} \right)}\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{t}^{−\frac{\mathrm{1}}{\mathrm{2}}} }{\mathrm{1}+\mathrm{e}^{\mathrm{t}} }\mathrm{dt}\:=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{t}^{−\frac{\mathrm{1}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{t}} }{\mathrm{1}+\mathrm{e}^{−\mathrm{t}} }\mathrm{dt} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{−\frac{\mathrm{1}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{t}} \sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \:\left(−\mathrm{1}\right)^{\mathrm{n}} \:\mathrm{e}^{−\mathrm{nt}} \:\mathrm{dt} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \left(−\mathrm{1}\right)^{\mathrm{n}} \:\int_{\mathrm{0}} ^{\infty} \:\mathrm{t}^{−\frac{\mathrm{1}}{\mathrm{2}}} \:\mathrm{e}^{−\left(\mathrm{n}+\mathrm{1}\right)\mathrm{t}} \:\mathrm{dt} \\$$$$=_{\left(\mathrm{n}+\mathrm{1}\right)\mathrm{t}=\mathrm{z}} \:\:\frac{\mathrm{1}}{\mathrm{2}}\sum_{\mathrm{n}=\mathrm{0}} ^{\infty\:} \left(−\mathrm{1}\right)^{\mathrm{n}} \:\int_{\mathrm{0}} ^{\infty} \left(\frac{\mathrm{z}}{\mathrm{n}+\mathrm{1}}\right)^{−\frac{\mathrm{1}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{z}} \:\frac{\mathrm{dz}}{\mathrm{n}+\mathrm{1}} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}}\sum_{\mathrm{n}=\mathrm{0}} ^{\infty} \:\left(−\mathrm{1}\right)^{\mathrm{n}} \:\frac{\mathrm{1}}{\left(\mathrm{n}+\mathrm{1}\right)^{\frac{\mathrm{1}}{\mathrm{2}}} }\int_{\mathrm{0}} ^{\infty} \:\mathrm{z}^{−\frac{\mathrm{1}}{\mathrm{2}}} \:\mathrm{e}^{−\mathrm{z}} \:\mathrm{dz} \\$$$$=\frac{\Gamma\left(\frac{\mathrm{1}}{\mathrm{2}}\right)}{\mathrm{2}}\sum_{\mathrm{n}=\mathrm{1}} ^{\infty\:} \:\:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}−\mathrm{1}} }{\mathrm{n}^{\frac{\mathrm{1}}{\mathrm{2}}} }\:=−\frac{\mathrm{1}}{\mathrm{2}}\sqrt{\pi}\delta\left(\frac{\mathrm{1}}{\mathrm{2}}\right) \\$$$$\delta\left(\mathrm{x}\right)=\sum_{\mathrm{n}=\mathrm{1}} ^{\infty} \:\frac{\left(−\mathrm{1}\right)^{\mathrm{n}} }{\mathrm{n}^{\mathrm{x}} }\:=\left(\mathrm{2}^{\mathrm{1}−\mathrm{x}} −\mathrm{1}\right)\xi\left(\mathrm{x}\right)\:\Rightarrow\delta\left(\frac{\mathrm{1}}{\mathrm{2}}\right)=\left(\mathrm{2}^{\frac{\mathrm{1}}{\mathrm{2}}} −\mathrm{1}\right)\xi\left(\frac{\mathrm{1}}{\mathrm{2}}\right) \\$$$$=\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)\xi\left(\frac{\mathrm{1}}{\mathrm{2}}\right).... \\$$